Fuzzy Adaptive Equalizer With Application To Power Line Communication Channel Equalization - Wong, Wai Kit (2006)
In this thesis, a new fuzzy adaptive equalizer(FAE) using extended Kalman filter (EKF) training algorithm is proposed for power line communication channel equalization.